Implementasi Pendekatan Pendidikan Multikultural Pada Pembelajaran IPS Kelas IV Dalam Mengembangkan Sikap Toleransi Siswa - ., Nur Halimah; ., Ludfi Arya wardana; ., Shofia Hattarina (CV. ITTC INDONESIA, 2023)
Multicultural education is an educational process that helps individuals develop ways of accepting, appreciating and participating in cultural systems that are different from their own. Research objectives 1) Describe the implementation of the multicultural education approach to social studies learning in developing students' cultural tolerance, student mutual cooperation tolerance, and student religious tolerance at Andungsari Elementary School. This research uses qualitative methods, research subjects use purposive techniques, data collection uses observation, interviews, and documentation. Data analysis uses the Hubermas and Miles models. The validity of the data using triangulation of sources and techniques. Research results 1) Implementation of a multicultural education approach to social studies learning in developing students' cultural tolerance through a culture of discussion. 2) Implementation of a multicultural education approach to Social Studies learning in developing students' mutual cooperation attitudes through cooperative activities 3) Implementation of a multicultural education approach to Social Studies learning in developing students' attitudes of religious tolerance a) respecting adherents of other religions, respecting fellow Muslims, b) Tolerance in religious activities Duha prayer in congregation.